Role of immune mediators in predicting hospitalization of SARS-CoV-2 positive patients. (February 2022) - Ashrafzadeh-Kian, S.; Campbell, M.R.; Jara Aguirre, J.C.; Walsh, J.; Kumanovics, A.; Jenkinson, G.; Rinaldo, P.; Snyder, M.R.; Algeciras-Schimnich, A.
Highlights: IL-6 is a predictive marker of the need for hospitalization and severity in COVID-19. Immune mediator profiles in hospitalized and non-hospitalized patients are distinct. Correlations between immune mediators differ between hospitalized and non-hospitalized groups. Abstract: Background: Several immune mediators (IM) including cytokines, chemokines, and their receptors have been suggested to play a role in COVID-19 pathophysiology and severity. Aim: To determine if early IM profiles are predictive of clinical outcome and which of the IMs tested possess the most clinical utility. Methods: A custom bead-based multiplex assay was used to measure IM concentrations in a cohort of SARS-CoV-2 PCR positive patients (n = 326) with varying disease severities as determined by hospitalization status, length of hospital stay, and survival. Patient groups were compared, and clinical utility was assessed. Correlation plots were constructed to determine if significant relationships exist between the IMs in the setting of COVID-19. Results: In PCR positive SARS-CoV-2 patients, IL-6 was the best predictor of the need for hospitalization and length of stay. Additionally, MCP-1 and sIL-2Rα were moderate predictors of the need for hospitalization. Hospitalized PCR positive SARS-CoV-2 patients displayed a notable correlation between sIL-2Rα and IL-18 (Spearman's ρ = 0.48, P=<0.0001). Conclusions: IM profiles between non-hospitalized and hospitalized patients were distinct. IL-6 was the best predictor of COVID-19 severity among all the IMs tested.